Mineral composition of repair raspberry (Rubus idaeus L.) fruits - S. M. Motyleva; S. N. Evdokimenko; M. A. Podgaetsky; T. A. Tumaeva; Y. V. Burmenko; N. Y. Svistunova; D. V. Panischeva; I. M. Kulikov (Вавиловский журнал генетики и селекции)
In recent years, raspberry breeding has shifted its emphasis from agronomic performance to characteristics related to the sensory qualities of the fruit and its potential health benefits. The therapeutic and preventive properties of raspberries are related to their biochemical composition. In this regard, the purpose of the work was to determine the content of macro- and micronutrients in fruits of different cultivars of repair raspberry using modern high-tech analytical methods and the selection of genetic sources of the analyzed elements for further breeding. The objects of the research were 17 cultivars of repair raspberry of different ecological and geographical origin from the genetic plant bioresource collection of FSBSO ARHCBAN. It was found that the ash residue of berries contains 12 major elements, which form the following descending series: K>P>Mg≥Mo>Ca>S≥Ni>Zn>Mn>Se>Fe≥Co. The largest proportion of ash residue in raspberry fruits is K. Depending on the cultivar, its quantity averaged from 12.81 wt % (Samorodok and Karamelka) to 22.37 wt % (Atlant). The minimum K content was observed in the ash of the Carolina cultivar (5.62 wt %), while in berries of this cultivar Mg (2.91), Ca (2.62) and Zn (0.14 wt %) accumulated above average. Among the group of early maturing cultivars, the cultivar Yubileinaya Kulikova stands out with a high content of Mo (4.63), Ca (2.19), Fe (0.25) and Co (0.21 wt %). The cultivar Pingvin is characterized by a high content of K (22.65) and Se (0.31 wt %). The medium maturity cultivar Samorodok is characterized by a higher content of P (4.08), S (0.47), Ni (0.51) and Zn (0.26 wt %). Among the late maturing cultivars, the cultivar Poranna Rosa stands out with the preferential accumulation of nine elements: Mg (2.98), P (4.42), S (0.36), K (20.34), Ca (1.71), Mn (0.14), Co (0.13), Se (0.21) and Mo (3.08 wt %). Correlation relationships between the elements have been established. Samples with the highest accumulation of macro- and microelements in berries represent genetic sources for further selection of raspberry for improvement of the mineral composition of fruits.